Gender equality in the workforce Reconciling work, private and family life in Europe - Mills, M; Tsang, F; Präg, P; Ruggeri, K; Miani, C; Hoorens, S (RAND Corporation, 2014)
This study examined the work, family and private life conflicts at different stages in one’s life course (from school-to-work transition to parenthood). We investigated the extent to which men and women face these challenges differently and examined their labour force participation, working hours, and contributions to household income and to domestic work. Throughout the report we observed improvements in gender equality over recent decades, but women continue to lag behind on labour force participation and earnings, face slower transition to their first job, while contributing more to domestic tasks even if they are breadwinners. These challenges are particularly pronounced in the presence of children. Mothers have lower employment rates, shorter hours and interrupted their careers more due to childcare, compared to women without children and men (with or without children).